2012
DOI: 10.1093/jxb/err449
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diurnal temperature variation on grape berry development, proanthocyanidin accumulation, and the expression of flavonoid pathway genes

Abstract: Little is known about the impact of temperature on proanthocyanidin (PA) accumulation in grape skins, despite its significance in berry composition and wine quality. Field-grown grapes (cv. Merlot) were cooled during the day or heated at night by +/–8 °C, from fruit set to véraison in three seasons, to determine the effect of temperature on PA accumulation. Total PA content per berry varied only in one year, when PA content was highest in heated berries (1.46 mg berry−1) and lowest in cooled berries (0.97 mg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(120 citation statements)
references
References 72 publications
7
109
3
1
Order By: Relevance
“…It is known that grapes grown in warmer climates have lower acidity than grapes grown in cooler climates. On the other hand, the warmer the climate the higher the sugar content of the grapes, so that alcohol degree will be higher The impact of increasing temperature on anthocyanin accumulation in grape skins has been indicated by some authors (Spayd et al 2002;Tarara et al 2008), and in particular, the effects of changes in day and night temperature (Cohen et al 2012). In this study, total and extractable anthocyanins did not show significant responses.…”
Section: Discussionmentioning
confidence: 39%
“…It is known that grapes grown in warmer climates have lower acidity than grapes grown in cooler climates. On the other hand, the warmer the climate the higher the sugar content of the grapes, so that alcohol degree will be higher The impact of increasing temperature on anthocyanin accumulation in grape skins has been indicated by some authors (Spayd et al 2002;Tarara et al 2008), and in particular, the effects of changes in day and night temperature (Cohen et al 2012). In this study, total and extractable anthocyanins did not show significant responses.…”
Section: Discussionmentioning
confidence: 39%
“…The first enzyme acts in the formation of proanthocyanidins (PAs), polymers of flavan-3-ol subunits, while the action of the second enzyme is linked directly through many avenues to the anthocyanin biosynthesis pathway (Table 1 and Additional file 9: Figure S6). Earlier reports in grape indicated that increased temperature enhances the production of PAs [52], which act in protecting plants against herbivores and UV radiation during the day [53]. The KEGG analysis in the anthocyanin biosynthesis pathway indicated the activation of only one enzyme, UDP-glucose:anthocyanidin (Table 1 and Additional file 9: Figure S6).…”
Section: Resultsmentioning
confidence: 93%
“…Wine samples from drier areas in Western China had lower content of total anthocyanins and higher contents of kaempferol derivates and hydroxycinnamic acids than wines produced with grapes cultivated in other regions (Li, Pan, Jin, Mu, & Duan, 2011). In addition to grape variety, some environmental factors such as temperature, ultraviolet radiation, and nutrient supply can affect the metabolism and regulate the gene expression of flavonoid in grapes (Cohen, Tarara, Gambetta, Matthews, & Kennedy, 2012;Martínez-Lüscher et al, 2014;Soubeyrand et al, 2014), leading to differences in the phenolic profile of wines and, consequently, in their by-products.…”
Section: Content Of Total Phenolic Compounds and Anthocyaninsmentioning
confidence: 99%